Model Of Children's Play Space Setting In The River Front Area In The Tambelan Sampit Cultural Village Area Post Construction Of The Waterfront Area In Pontianak City - R. Puspito Harimurti; Muhammad Radhi Muhammad Radhi; Wahyudin Ciptadi Wahyudin Ciptadi; Nur Syam Nur Syam (Politeknik Negeri Pontianak, 2025)
Abstract This study aims to formulate patterns and models of children's play areas in the Tambelan Sampit Cultural Village Area riverbank that support cultural activities and the Pontianak City program as a Child-Friendly City after the Waterfront Development. The study uses a descriptive-qualitative method through a rationalistic-qualitative approach to setting children's play areas in the riverbank area. The study results indicate that the setting of children's play areas is dominated by gliding and water games (swimming and diving competitions). Personal space in the area is influenced by age, mood, and gender. The territorial markers of the area are in the form of medium to shallow water areas and low tide conditions, are non-verbal, and are still traditional. 1-14 children play the game in a dynamic area and with an open level of privacy. Behavior control through territoriality is a type of privacy that tends to be reserved. The territory in the children's play area setting is generally classified as a public territory with low ownership cognition and is personalized only when playing. From this study, it can be concluded that there are three types of children's play areas in this area, namely (a) play areas on village roads (including the Waterfront promenade area), (b) yards, and (3) riverbanks. Children tend to use the areas available in their environment to support their relatively safe play activities, namely in the shallow areas of the riverbanks along the waterfront, house terraces, and neighborhood roads. Games tend to adapt to the conditions of the place determined by the user group based on age, physical size, gender of the child, proximity to residence, types and patterns of games played by people, and availability of time.